A constituição do ensino de língua portuguesa em textos introdutórios de livros didáticos dos anos 1960 a 1980 - Rodrigues, Nina Rosa Licht (2012)
The current dissertation paper has as aim to investigate the responsive attitudes from the authors upon Portuguese teaching and language studies in introductory texts from Portuguese textbooks in the 1960s, 1970s and 1980s. We consider, as methodological and theoretical framework, the social-historic theory, such as developed by Bakhtin Circle. The statements were described, analyzed and interpreted taking into account the social and historical moment in which the authors words were constructed and the dialogical relations, that are meaning relations. From the analyses done and the dialogical relations established, we identified more similarity to the traditional discourse on language teaching rather than distinction, demonstrating that the majority of the authors follow the tradition of language studies; except in the statements from the 1980s, in which the author do not fit in this teaching and language study. We noticed also that each statement follows the stabilization and hegemony movement, over time, after beginning the gradual incorporation of discourses from Linguistics science until reaching a specific historical moment, in which proposals and practices of traditional teaching exclusion intensify themselves and gain expression